MANAJEMEN PEMBELAJARAN ENGLISH AREA DI LINGKUNGAN GURU MTS AL-MUTTAQIN SURABAYA - nuriya, Nuriya Shofa; M. Athoiful Fanan (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
This study aims to determine the Management of English Area Learning in the Teachers' Environment of MTs Al Muttaqin and to find out the barriers to English Area learning in the teachers' environment of MTs Al-Muttaqin and the supporting factors of English Area in the teachers' environment of MTs Al-Muttaqin. This research uses qualitative research methods or field research located at MTs Al Muttaqin Surabaya. The research data sources used in this study are primary and secondary data sources. Primary data sources were obtained from interviews with MTs Al Muttaqin teachers. Secondary data sources are obtained from the results of documentation in the form of a description of the research location and a brief history, organisational structure, and teacher conditions. The results of research in English Area learning management in the environment of MTs Al-Muttaqin Surabaya teachers are quite good because they have carried out activities which include pre-test speaking, English learning and learning evaluation.Learning inhibiting factors are teachers who are still teaching in the classroom. The supporting factor is the enthusiasm of teachers to follow English learning and the principal who supports the English learning programme. In conclusion, learning management is carried out with stages: learning planning, organising, directing and evaluating. In these activities, English Area learning management in the environment of MTs Al-Muttaqin teachers has carried it out well and in accordance with the theory of indicators that researchers use. So that the teaching and learning process runs effectively and efficiently.